Sexual violence and associated factors among reproductive-age females with disabilities in central Sidama National Regional State, Ethiopia: a multilevel analysis - Zelalem Tenaw; Taye Gari; Achamyelesh Gebretsadik (BMC, 2023)
Abstract Background Sexual violence is one of the most common problems in reproductive health that causes different traumatic events that lead to mental, social, and physical problems. Females with disabilities are subjected to more traumatic events and consequences. In Ethiopia, there are limited evidences about the prevalence and associated factors of sexual violence among reproductive-aged females with disabilities. Therefore, this study aimed to assess the prevalence and associated factors of sexual violence among females with disabilities in reproductive-age in central Sidama National Regional State, Ethiopia. Methods A multistage sampling technique was used to select 645 reproductive-age females with disabilities. Initially, three districts were purposefully selected, from which 30 kebeles and study participants were selected randomly from June 20 to July 15, 2022. A face-to-face interviewing technique was used to collect the data. The data were analyzed using a multilevel logistic regression analysis model. The measures of associations were reported using the adjusted odds ratio (AOR) and its 95% confidence interval (CI). Results The prevalence of sexual violence among reproductive-age females with disabilities was 59.8% (95% CI: 56, 63.56). Residing in an urban setting (AOR = 0.51; 95% CI: 0.29, 0.88), being an adult (25 to 34 years old) (AOR = 5.9; CI: 3.01, 11.6), being an adult (35 to 49 years old) (AOR = 3.47; CI: 1.48, 8.14), having no sexuality information (AOR = 11.3; CI: 6.24, 20.5), and having hearing disabilities (AOR = 3.19; CI: 1.49, 6.83) were factors associated with sexual violence. Conclusions Sexual violence among reproductive-age females with disabilities is noticeably high. Place of residence, sexual orientation, age, and disability type were all factors associated with sexual violence. Therefore, providing sexuality education, giving high attention (information and education about sexuality) to rural residents, and considering females with hearing disabilities are important to minimize sexual violence among reproductive-age females with disabilities.